Subpicosecond pulse generation at quasi-40-GHz using a passively mode-locked AlGaInAs-InP 1.55-µm strained quantum-well laser - Hou, L.; Stolarz, P.; Javaloyes, J.; Green, R.; Ironside, Charlie; Sorel, M.; Bryce, A. (2009)
We report on subpicosecond pulse generation using passively mode-locked laser diodes based on AlGaInAs 1.55-µm strained multiquantum-wells. Without any external pulse compression, the nearly transform-limited Gaussian pulses are generated at the quasi-40-GHz repetition rate with the 700-fs pulse duration. © 2009 IEEE.